Development and Validation of Ultraviolet Spectrophotometric Method for Estimation of Frovatriptan Succinate Monohydrate in Bulk and Pharmaceutical Dosage form - Narang, Dr. Jasjeet Kaur (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The research explains the simple, robust, and rapid spectrophotometric method for the estimation of frovatriptan succinate monohydrate (FSM) as API and in films forms. Materials and Methods: FSM was determined by ultraviolet-visible double-beam spectrophotometer at 244 nm as wavelength maxima in pH 6.8 simulated salivary fluid. The developed method was validated by taking parameters according to the ICH Q2 (R1) guidelines. Results and Discussion: Beer’s law was found to be obeyed in the concentration range of 0.1–8 μg/ml with a correlation coefficient of 0.99. Percentage relative standard deviation for all validation parameters was found to be <2%. This analysis method was successfully applied for the determination of FSM in sublingual film dosage forms. Conclusion: The results demonstrate that the developed method is accurate, precise, robust, and reproducible, and hence, the developed spectrophotometric method can be used for analysis of FSM in bulk and other pharmaceutical dosage forms.